2009
DOI: 10.1055/s-0039-1699316
|View full text |Cite
|
Sign up to set email alerts
|

Current concepts in genetics of nonsyndromic clefts

Abstract: Nonsyndromic cleft lip and palate is a complex genetic disorder with variable phenotype, largely attributed to the interactions of the environment and multiple genes, each potentially having certain effects. Numerous genes have been reported in studies demonstrating associations and/or linkage of the cleft lip and palate phenotypes to alleles of microsatellite markers and single nucleotide polymorphisms within specific genes that regulate transcription factors, growth factors, cell signalling and detoxificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 78 publications
0
15
1
Order By: Relevance
“…3). Our result here is divergent to widely reported higher left sided unilateral clefts than rightsided CLs [27][28][29]. Majority (40.4%) of CL/P were located bilaterally.…”
Section: Discussioncontrasting
confidence: 99%
“…3). Our result here is divergent to widely reported higher left sided unilateral clefts than rightsided CLs [27][28][29]. Majority (40.4%) of CL/P were located bilaterally.…”
Section: Discussioncontrasting
confidence: 99%
“…Current estimates support the hypothesis that as many as 14 possibly interacting genes contribute to CL/P development (Schliekelman and Slatkin,2002). Analyses of candidate loci and genome‐wide linkage scans have shown a wide range of plausible candidate genes or regions for clefts (Carinci et al,2007; Murthy and Bhaskar,2009). However, these genetic findings can explain only a small portion of the genetic component contributing to the pathogenesis of CL/P.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic screens for nucleotide variants of more than 20 CL/P candidate genes such as MSX1 , FOXE1 , GLI2 , JAG2 , LHX8 , or STAB2 have shown that merely 2 to 6% of the total number of individuals with CL/P have mutations in these genes (Jezewski et al,2003; Vieira et al,2005). In addition, multiple candidate gene association studies have identified polymorphic variants that influence the risk of CL/P (Lidral and Moreno,2005; Murthy and Bhaskar,2009). Nevertheless, levels of etiologic heterogeneity underlying CL/P are a reason of common discrepancies in results obtained across these studies, which were conducted in various populations with different ethnic groups.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic alterations are thought to contribute to ∼20 to 25% of CP cases (Marazita, ; Lidral and Moreno, ) while environmental factors represent contributing factors in the remaining cases. Analyses of mutations indicate that many of the genes responsible for palate development encode transcription factors, growth and signaling molecules and their receptors, and ECM (extracellular matrix) components (reviewed in Cobourne, ; Murray and Schutte, ; Stanier and Moore, ; Lidral and Moreno, ; Rice, ; Carinci et al, ; Gritli‐Linde, ; Juriloff and Harris, ; Jugessur et al, ; Murthy and Bhaskar, ; Vieira, ; Yu et al, ; Bush and Jiang, ). Several of these genes are members of key signal transduction pathways required for palate development.…”
Section: Introductionmentioning
confidence: 99%